Peran Guru Dalam Mengembangkan Kemampuan Berpikir Kritis Siswa - Aqila Sahla Fadhilatunnisa; Febrian Alwan Bahrudin (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
cation plays a crucial role in shaping human resources capable of facing the complexities of the 21st century. One of the essential skills students must develop is critical thinking, which is vital not only for academic success but also for daily life. Developing critical thinking skills requires teachers to possess strong pedagogical competencies in designing challenging, reflective, and contextual learning experiences. However, in practice, many teachers encounter obstacles such as limited time, administrative burdens, and a lack of understanding of effective learning strategies. Implementing discussion-based, debate-based, problem-solving, project-based, and problem-based learning strategies can enhance students’ critical thinking abilities. Furthermore, the integration of educational technology is essential to create interactive and adaptive learning environments. Teachers act as facilitators and agents of change who encourage students to think analytically, reflectively, and innovatively. Thus, strengthening critical thinking skills supports the achievement of national educational goals in developing individuals who are faithful, knowledgeable, creative, and competitive in the global era.